Temperature dependences of optical properties, chemical composition, structure, and laser damage in Ta2O5 films - 许程 杨帅 张生辉 牛继南 强颖怀 刘炯天 李大伟 (中国物理B：英文版, 2012)
Ta2O5 films are prepared by e-beam evaporation with varied deposition temperatures, annealing temperatures, and annealing times. The effects of temperature on the optical properties, chemical composition, structure, and laser- induced damage threshold （LIDT） are systematically investigated. The results show that the increase of deposition temperature decreases the film transmittance slightly, yet annealing below 923 K is beneficial for the transmittance. The XRD analysis reveals that the film is in the amorphous phase when annealed below 873 K and in thehexagonal phase when annealed at 1073 K. While an interesting near-crystalline phase is found when annealed at 923 K. The LIDT increases with the deposition temperature increasing, whereas it increases firstly and then decreases as the annealing temperature increases. In addition, the increase of the annealing time from 4 h to 12 h is favourable to improving the LIDT, which is mainly due to the improvement of the O/Ta ratio. The highest LIDT film is obtained when annealed at 923 K, owing to the lowest density of defect.